A copper-metal organic framework enhances the photothermal and chemodynamic properties of polydopamine for melanoma therapy. (1st March 2023) - Liu, Lidan; Zhang, Haifeng; Peng, Luxi; Wang, Donghui; Zhang, Yu; Yan, Bangcheng; Xie, Juning; Xing, Shun; Peng, Feng; Liu, Xuanyong
Abstract: The combination of photothermal treatment and chemodynamic therapy has attracted extensive attention for improving therapeutic effects and compensating the insufficiency of monotherapy. In this work, a copper-metal organic framework (Cu-BTC) was used to augment the photothermal effect of polydopamine (PDA) and endow it with a chemodynamic ability by constructing a Cu-BTC@PDA nanocomposite. Density functional theory calculations revealed that the plasmonic vibrations formed by the d-d transition of Cu at the Fermi level in Cu-BTC@PDA could enhance the photothermal performance of PDA. In addition, more Cu 2+ released from Cu-BTC@PDA in the acidic microenvironment of the tumor was then reduced to Cu + by glutathione (GSH) and further catalyzed H2 O2 to generate more toxic hydroxyl radical (OH), which synergized with photothermal treatment for melanoma therapy. Furthermore, Cu-BTC@PDA could quickly and effectively kill bacteria under the action of PTT, and the sustained release of Cu ions could contribute to the long-term and stable bacteriostatic ability of the material. This sustained release of Cu ions could also promote the cell migration and angiogenesis, and upregulate the expression of COL -, TGF -, and VEGF -related genes to accelerate wound healing. This multifunctional nanomaterial has potential application in the treatment of melanoma and repair of wounds. Statement of significance: We constructed a multifunctional nanoplatform (Cu-BTC@PDA) by two steps. This nanoplatform can not only perform cascade catalysis in the tumor microenvironment to generate more toxic hydroxyl radical (OH), but also synergize with photothermal treatment for melanoma therapy. Additionally, Cu-BTC@PDA possesses enhanced photothermal performance through the plasmonic vibrations formed by the d-d transition of Cu at the Fermi level in Cu-BTC@PDA, which is revealed by DFT calculations. And Cu-BTC@PDA shows good antitumor, antibacterial, and wound healing properties in vivo and in vitro . Such a multifunctional nanomaterial has potential application in the treatment of melanoma and repair of wounds. Graphical abstract: Image, graphical abstract